Application of artificial intelligence in the Internet of Things: a documentary study (MASKAY, 2025)
The convergence of the Internet of Things (IoT) and Artificial Intelligence (AI) has catalyzed substantial advancements across multiple sectors, including agriculture, security, healthcare, home automation, and resource management. This paper presents a systematic literature review aimed at identifying key applications, AI techniques, and benefits resulting from the integration of these technologies. The review process was conducted in accordance with the PRISMA methodology, encompassing publication selection, data extraction, and analysis. Out of 725 initially retrieved records, 53 studies were selected for detailed examination. The results indicate that multisensor systems represent 28.85% of the reported applications, followed by IoT security (21.15%) and smart cities (15.38%). In terms of AI techniques, multisensor data fusion was the most frequently employed (40.38%), followed by deep neural networks (19.23%) and support vector machines (15.38%). Most of the reviewed studies report accuracy levels of 90% or higher. These findings highlight the critical role of AI in enhancing IoT systems and identify the domains with the highest potential for future development.
Keywords: IoT; AI; machine learning; prediction algorithms